2019
DOI: 10.1055/s-0039-1678719
|View full text |Cite
|
Sign up to set email alerts
|

To Maintain or Cease Non–Vitamin K Antagonist Oral Anticoagulants Prior to Minimal Bleeding Risk Procedures: A Review of Evidence and Recommendations

Abstract: For procedures associated with minimal bleeding risk, there are data and experience to support the practice of continuing vitamin K antagonists rather than interrupting therapy, to prevent exposing patients to the undue risk of developing thromboembolism during anticoagulation cessation. Despite the increasing use of non–vitamin K oral anticoagulants (NOACs), there is little evidence to guide the management of these drugs around minimal bleeding risk procedures. This review examines and discusses the major soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…A study of 117 procedures with dagabigatran continuation reported one haemarthrosis (Guillen-Astete et al, 2017). The current study adds to this accumulating evidence of safety that continuation of DOACs is a low risk strategy with musculoskeletal procedures against the risks with interruption (Brennan et al, 2019;Kotecha et al, 2022;Tarar et al, 2021).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 80%
“…A study of 117 procedures with dagabigatran continuation reported one haemarthrosis (Guillen-Astete et al, 2017). The current study adds to this accumulating evidence of safety that continuation of DOACs is a low risk strategy with musculoskeletal procedures against the risks with interruption (Brennan et al, 2019;Kotecha et al, 2022;Tarar et al, 2021).…”
Section: Direct Oral Anticoagulantsmentioning
confidence: 80%
“…Oozing or marked hemorrhaging persisting from 24 h to 7 days after dental extraction that required treatment to arrest bleeding Brennan et al (2019) Bleeding that required medical intervention by a health care provider including oral anticoagulant discontinuation, bleeding that led to hospitalization or increased level of care without requiring surgical intervention, and bleeding that led to face-toface evaluation Berton et al (2019) Bleeding that required compression packs, pharmacological intervention or surgical intervention Yoshikawa et al (2019) Oozing or marked haemorrhage that could not be stopped by wound compression with gauze, and haemostasis that required medical intervention such as haematoma removal, curettage, suturing, or splint placement Lababidi et al (2018) Bleeding managed with direct measures such as pressure at home or by a clinician Yagyuu et al (2017) Bleeding that could not be stopped by biting down on gauze and that required medical treatment between 30 min and 7 days after the tooth extraction Caliskan et al (2017) Bleeding managed with gauze pads, hemostatic agents or bleeding requiring hospitalization Mauprivez et al (2016) Persistent oozing or marked hemorrhage over 20 min after tooth extraction despite local hemostasis procedures or all bleeding episode occurring during the first postoperative week profile of DOAC, have been concerns amongst clinicians regarding the reversibility of these agents in case of severe bleeding. While reversal agents like andexanet alfa have recently been developed, the cost and availability is still a limiting factor (Frontera et al, 2020).…”
Section: Inokoshi Et Al (2021)mentioning
confidence: 99%
“…It is now well-established that uncomplicated dental extractions can be safely carried out without interruption of VKAs therapy provided INR is maintained <3.5 and local hemostatic measures are performed to control bleeding (Nematullah et al, 2009). However, no clear guidelines exist on the perioperative management of patients receiving DOAC (Brennan et al, 2019). Recommendations range from the continuation of DOAC during dental extractions to omitting one or two doses of the drug before the procedure (Brennan et al, 2019).…”
Section: Inokoshi Et Al (2021)mentioning
confidence: 99%
See 1 more Smart Citation